2022
DOI: 10.1021/acs.jpcb.1c07951
|View full text |Cite
|
Sign up to set email alerts
|

Excimer Formation Inhibits the Intramolecular Singlet Fission Dynamics: Systematic Tilting of Pentacene Dimers by Linking Positions

Abstract: The role of excimer formation in inhibiting or enhancing the efficiency of the intramolecular singlet fission (iSF) process has been a subject of recent debate. Here, we investigated the effect of excimer formation on iSF dynamics by modifying its configuration by connecting pentacenes at various positions. Hence, pentacene dimers having slip-stacked (2,2′ BP, J-type), oblique (2,6′ BP), and facial (6,6′ BP, H-type) configurations were synthesized by covalently linking pentacenes at positions 2,2′, 2,6′, and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…The authors found that as the distance between the pentacene molecules was reduced, i.e., as spacer groups were removed, both the time scales of triplet pair formation and decay also decreased, with the shortest triplet pair lifetime measured at ∼450 ps. A similar relationship was recently observed by Paul and Karunakaran in bipentacenes covalently linked at their 2,2′-, 2,6′-, and 6,6′-positions with an ethynyl bridge . Sanders et al also observed that the bipentacene with the longest spacer exhibited a triplet pair lifetime of ∼270 ns.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The authors found that as the distance between the pentacene molecules was reduced, i.e., as spacer groups were removed, both the time scales of triplet pair formation and decay also decreased, with the shortest triplet pair lifetime measured at ∼450 ps. A similar relationship was recently observed by Paul and Karunakaran in bipentacenes covalently linked at their 2,2′-, 2,6′-, and 6,6′-positions with an ethynyl bridge . Sanders et al also observed that the bipentacene with the longest spacer exhibited a triplet pair lifetime of ∼270 ns.…”
Section: Resultssupporting
confidence: 83%
“…A similar relationship was recently observed by Paul and Karunakaran in bipentacenes covalently linked at their 2,2′-, 2,6′-, and 6,6′-positions with an ethynyl bridge. 57 Sanders et al also observed that the bipentacene with the longest spacer exhibited a triplet pair lifetime of ∼270 ns. These results were consistent with Lukman et al, who synthesized an orthogonal pentacene dimer and observed a similarly short triplet pair lifetime of ∼650 ps, which could be extended in certain polymer matrices to as long as ∼140 ns.…”
Section: Resultsmentioning
confidence: 94%
“…69 On the other hand, excimer formation can also be utilized to suppress SF. 70,71 To expand the library of viable annihilators and demonstrate that triplet generation the perovskite/ OSC interface is a universal process not inherently limited to the perovskite/rubrene interface, we have recently reported solid-state near-infrared-to-visible UC using a FAMA sensitizer and 1-CBPEA annihilator, which enables UC from near-infrared (800 nm) to green (550 nm) as shown in Fig. 2.…”
Section: Introductionmentioning
confidence: 99%
“…assemblies, excimer formation is unfavorable and is considered as a trap state that hinders the desired energy or charge transfer processes. 25 Fresh perspectives were reported recently that an excimer does not always dissipate excited energy. Instead, they can be in a positively premeditated state of charge separation or singlet fission in some materials.…”
mentioning
confidence: 99%
“…In most rylene dimers, strong polar solvent environments are generally more beneficial to charge separation than weak polar or nonpolar solvent environments. People have different opinions on the composition of an excimer, a typical intermediate species of excited dynamics in aggregates, and whether it plays a positive role in SB-CS. In some molecular assemblies, excimer formation is unfavorable and is considered as a trap state that hinders the desired energy or charge transfer processes . Fresh perspectives were reported recently that an excimer does not always dissipate excited energy.…”
mentioning
confidence: 99%